Quality of Public Library Services as Predictors of BARMM Community’s Information Needs Satisfaction (British Journal of Multidisciplinary and Advanced Studies, 2024)
Public libraries have always been a source of essential information resources in the community. This descriptive-correlational research was conducted to examine the quality of library services and its influence on the information needs satisfaction of the BARMM community.  Specifically, this research determined the library user's assessment of the quality of BARMM's public libraries in terms of; availability of resources; accessibility of resources; availability of technology; library staff competence and library atmosphere, and the extent of the library user's information needs satisfaction considering educational needs, professional needs, religious needs and community development needs. Data were collected using validated and pilot-tested questionnaires. The data were analyzed using descriptive and inferential statistics. Based on the findings, the participants' information needs were generally satisfied. Moreover, the participant's assessment of the BARMM's public libraries significantly influenced their information needs satisfaction. The study points to giving special attention to the accessibility of resources and implementing advanced technology in BARMM public libraries to attract more users and promote lifelong learning within the community.